Dermoscopic appearance of an amelanotic mucosal melanoma - Andreas Blum; Ulrike Beck-Zoul; Laura Held; Sylvie Haase (Dermatology Practical & Conceptual, 2016)
Background: Hypomelanotic or amelanotic melanomas are challenging to identify, especially at mucosal sites. The dermoscopic clues to the diagnosis of mucosal melanomas have been reported to be structureless zones with the presence of blue, gray, or white colors.